Eicosanoid Protocols - Lianos, Elias A.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1999)
In Eicosanoid Protocols, Elias A. Lianos and a panel of hands-on experts present cutting-edge methods for the study of eicosanoids, including prostaglandins, thromboxanes, and leukotrienes. The readily reproducible methods described hereconcentrate on studying the regulation of expression and function of enzymes, particularly cyclooxygenase (and its two isoforms), phospholipase A2, and lipoxygenases involved in the synthesis of established eicosanoids. Additional chapters are devoted to the characterization and distribution of the thromboxane A2 receptor in tissues and the biological roles of novel eicosanoids. Timely and authoritative, the methods in this book will help their users in exploring the pathobiology of inflammation. Eicosanoid Protocols offers new and established researchers powerful, state-of-the-art tools to probe the regulation and function of eicosanoids.
Use of a Retroviral Vector for Expression of a Foreign Gene -- Extraction of Eicosanoids from Biological Fluids, Cells, and Tissues -- Assessment of Cyclooxygenase RNA Expression by Northern Hybridization -- Immunohistochemical Analysis of Cyclooxygenase Expression in Human Skin -- Separation of Hydroxyeicosatetraenoic Acids and Leukotrienes Originating from Kidney Tissue by C-18 Reverse-Phase High-Pressure Liquid Chromatography -- Localization and Distribution of Cyclooxygenase-2 in Brain Tissue by Immunohistochemistry -- Assessment of Cyclooxygenase Protein Expression by Western Blotting -- Assessment of Arachidonic Acid Distribution into Phospholipids of Inflammatory Cells -- Determination of Phospholipase A2s Expression in Mast Cells by Reverse-Transcriptase Polymerase Chain Reaction -- Enzyme immunoassays (EIA) of Eicosanoids -- Transcellular Regulation of Eicosanoid Biosynthesis -- Assessment of Cellular Localization of the Thromboxane A2 Receptor by Immunocytochemistry -- Epoxyeicosatrienoic Acids -- Assessment of the Expression of Prostaglandin Synthase-2 in Swiss 3T3 Fibroblasts -- Assessment of 5-Lipoxygenase Activity and Cellular Distribution -- Leukotrienes, Lipoxins, and Hydroxyeicosatetraenoic Acids -- Whole Blood Assays for Evaluation of Thromboxane Synthase Inhibition -- Novel Eicosanoids.
Keywords: Biochemistry; Biochemistry, general